Removal of Methylene Blue from Aqueous Effluent Using Fixed Bed of Groundnut Shell Powder - Sunil Kumar; V. Gunasekar; V. Ponnusami (Journal of Chemistry)
Removal of methylene blue from aqueous solution using a low-cost adsorbent groundnut shell powder (GNSP) was studied using fixed bed. Bed service depth model and Thomas model were employed to study the adsorption kinetics and to predict break-through curves for the system. Both models fit the experimental data very well with very high R2 values. Percentage color removal increased with increase in bed height. It was found that adsorption potential of GNSP was in the range of 0.238 to 0.272 kg/kg of adsorbent. These results show that the GNSP can be effectively used as low-cost alternate adsorbent for the removal of pollutants from aqueous streams.